Upaya Meningkatkan Hasil Belajar Ekonomi Dengan Menggunakan Metode Pembelajaran Learning Start With A Question Pada Perserta Didik - Nopi, Nopi; Nurbudiyani, Iin (Neraca: Jurnal Pendidikan Ekonomi, 2017)
This study aims to determine the Activity and Enhancement of student learning outcomes in economic learning using the Lesing Start With A Question (LSQ) method. The subjects in this study were all participants of the X-11 class of SMA 3 Palangka Raya, which numbered 40 people, where data collection used observation and test sheets. The results of the study show that the activities and learning outcomes of students appear to be more active and increasingly higher by using the Learning Start With A Question (LSQ) Method on Economics subjects. It was proven that the pre-action learning results obtained an average value of 62.88 including in the criteria not achieved, then in the first cycle it increased, with an average value of 78.5 which was included in the category not achieved with classical completeness of 52.5% and referred to in the category achieved. Cycle II with an average value of 91 referred to in the category has been achieved and classical completeness obtained 87.5% or 35 students participating in studying economics with statement material based on the content of the text.